(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
This paper aims to study and optimize a new configuration of an inclined-plane-type electrostatic separator. The device consists of two inclined planes arranged in a cascade. The design is aimed at efficiently separating millimeter-sized particles, specifically polycarbonate (PC) and polyamide (PA). Preliminary experiments were conducted to investigate the effects of various operating parameters on separation efficiency, including tribo-electric charging time, fluidizing air speed, and the angle between the high-voltage electrodes. The design of experiments (DOE) methodology was employed to model the outcome of the separation process, focusing on two control variables: the length of the electrodes generating the electric field and the applied voltage level. The results revealed the existence of optimal values, resulting in a product recovery rate of 97 %, with high purity levels (98 % for PC and 96% for PA).